Implementasi Sensor Kelembapan Tanah Penyiram Tanaman Otomatis Berbasis Mikrokontroler Dengan IoT - Yudiana, Teddy Trisnanda Yudiana; Patma, Tundung Subali; Fauziyah, Mila (Jurnal Elektronika dan Otomasi Industri, 2024)
Abstract— Plants are living things that need water for growth, so plant growth is also very influential on the amount of water and nutrients that can be absorbed properly in the growth process. Plants themselves get water through the soil that is absorbed by the roots, but rooted plants such as mustard greens, tomatoes, chilies, and other vegetables find it difficult to reach deeper water. In order to maintain the quality of soil moisture so that it remains stable, special handling is needed, namely regular watering by paying attention to the percentage of water content that ranges from 60% -80%. In today's era, technology is increasingly advanced but many people do not use it to its full potential. For example, filling the water tank still uses the old way, namely by connecting cables and turning on the water pump manually. Likewise, the plant watering system that is still manual must turn on the water faucet. This is considered ineffective because maintenance of cable maintenance is difficult, especially since the distance between the water tank and the water pump is far and it also requires energy to control the plant. Therefore, this research tool was made using an Ultrasonic Sensor as a water depth reader,a Soil Moisture Sensor as a reader of soil moisture so that it is controlled to keep humidity at 60%-80%, using a NodeMCU microcontroller as a link between the tank and the tank filling controller and also watering plants. With this system, it can help human performance so that they don't have to fill manual water tanks that require cables and also irrigate dry plants. Keywords: Plant, Sensor, Soil Moisture, Ultrasonic Sensor, NodeMCU, Microcontroller